Assessing the Potential of Open Educational Resources for Open and Distance Learning - Leeds, Beverly (South African Journal of Higher Education, 2016)
This paper provides a critical assessment of the potential of Open Educational Resources (OER) for Open Distance Learning (ODL). After providing a definition it provides a discussion about the nature of OER and explores the growth of the OER community. It also examines the different meanings that ‘open’ has when dealing with OER and ODL before exploring the opportunities and possibilities that OER afford. The paper examines whether OER can assist in the higher education crisis in terms of available places and that it can also contribute to sustainable global economic growth. It also draws attention to the dark side of OER adoption, such as information imperialism and the danger that developing nations may only be consumers not producers of OER. It concludes by highlighting the potential of OER in ODL and draws attention to the need for specific educational practices and actions to facilitate the use of OER in ODL.